Association between occupational stress and subclinical depression in Chinese primary healthcare workers - Zhang, Jiao; Xu, Lingzhong; Qin, Wenzhe; Xu, Aijun (Frontiers in Psychiatry, 2023)
Background Wellbeing of healthcare workers is crucial for the effective functioning of primary health systems. This study aimed to examine the association between occupational stress and subclinical depression among primary healthcare workers, and to establish the foundation for future preventive strategies. Methods A cross-sectional study was conducted in Tai’an City, Shandong Province, China. Data were collected from 832 medical staff in primary health institutions using a structured self-administered questionnaire. The participants completed the Challenge and Hindrance-Related Self-Reported Stress (C-HSS) Scale and Patient Health Questionnaire-9. Multivariable logistic regression analysis was conducted to explore the relationship between occupational stress and subclinical depression among primary healthcare workers. Results The prevalence of subclinical depression among primary healthcare workers was 11.66%. Participants with subclinical depression have a significant higher level of occupational stress (including challenge-stress and hindrance-stress). Regression analysis result indicated that higher level of occupational stress was significantly associated with more severe subclinical depression, and the risk of subclinical depression remained after adjusting other covariates (OR = 4.57, 95%CI, 3.14–6.63). The association between challenge-stress and subclinical depression was not statistically significant when controlling for hindrance-stress. Subgroup analysis showed that male healthcare workers who perceived higher level of challenge stress were more likely to develop subclinical depression than female healthcare workers. Conclusion The level of subclinical depression among Chinese primary healthcare workers was high, and occupational stress especially hindrance stress may contribute to subclinical depression. Findings were also robust in subgroup analysis after adjusting for other covariates. These findings emphasize the importance of occupational stress psychosocial interventions to decrease the risk of developing depression among the primary healthcare workers.